2022
DOI: 10.1080/10717544.2022.2039802
|View full text |Cite
|
Sign up to set email alerts
|

Anti-photoaging effects of flexible nanoliposomes encapsulated Moringa oleifera Lam. isothiocyanate in UVB-induced cell damage in HaCaT cells

Abstract: Skin photoaging is premature skin aging damage that occurs after repeated exposure to ultraviolet (UV) radiation. Although isothiocyanates extracted from the moringa tree ( Moringa oleifera Lam. ) (MITC) exhibit excellent effects against skin photoaging, its application is restricted because of its characteristics, such as extremely low water solubility, bioavailability, and easy degradation. Currently, flexible nanoliposomes have gained increasing interest as a biocompatible polymer for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…By using this method, unstable liquid compounds can be converted into free-flowing stable powder. Core bioactive components have been encapsulated using a variety of techniques, including cross-linking gelation, freeze-drying, microemulsion, spray drying, and different nanoformulations (nanoliposomes) ( Figure 3 ) [ 72 , 73 , 74 ].…”
Section: Encapsulation Methods Of Bioactive Compounds From ...mentioning
confidence: 99%
“…By using this method, unstable liquid compounds can be converted into free-flowing stable powder. Core bioactive components have been encapsulated using a variety of techniques, including cross-linking gelation, freeze-drying, microemulsion, spray drying, and different nanoformulations (nanoliposomes) ( Figure 3 ) [ 72 , 73 , 74 ].…”
Section: Encapsulation Methods Of Bioactive Compounds From ...mentioning
confidence: 99%
“…To investigate the permeation-enhancing mechanism of the HPCD-Lipo formulation, we analyzed the treated skin by FTIR and Raman analyses. Generally, three regions with related to barrier function are often investigated in the transdermal study, including (1) IR absorbance at 2920 and 2850 cm –1 representing asymmetric vibration (ν as CH 2 ) and symmetric stretching vibration (ν s CH 2 ) of the methylene groups of intercellular lipids, (2) vibrations of amide I (1640 cm –1 ) and amide II (1550 cm –1 ) bands related to the SC keratin that is distinct from the ceramide amide bond in the skin (1612 cm –1 ), and (3) the peaks ranging 1060–1130 cm –1 related to the fluidity of skin lipids. The HPCD/QT Lipo@gel treatment resulted in a red shift of both ν as CH 2 (from 2916 to 2925 cm –1 ) and ν s CH 2 (from 2849 to 2852 cm –1 ) (Figure B). The red shift of ν as CH 2 and ν s CH 2 indicated that the orderly arrangement of the skin matrical lipids was compromised .…”
Section: Resultsmentioning
confidence: 99%
“…13–15 Furthermore, the isothiocyanates contained in M. oleifera seeds also play a crucial role in anti-inflammatory, antioxidant, antibacterial and anticancer. 16 And the essential oil has coagulant effect that can accelerate wound healing. 17…”
Section: Medicinal Parts Of M Oleiferamentioning
confidence: 99%